Traumatic neuroma of the superficial peroneal nerve in a patient: a case report and review of the literature. Issue 1 (December 2016) - Kang, Jian; Yang, Pinglin; Zang, Quanjin; He, Xijing
Abstract Background Traumatic neuromas are rare benign tumors, which are common in trauma or post-operation and accompanied with obvious symptoms of pain. This study will show the superficial peroneal nerve neuroma occurring after resection of hemangioma. Case presentation A 44-year-old male had an operation of the right leg cavernous hemangioma resection in 1995. Half a year after the operation, pain around the wound appeared and gradually aggravated. The patient had the lesion exploration resection in 2013, and the pathological result showed traumatic neuroma. Within half a year of the second operation, severe pain showed up again, so neuroma resection proceeded in May 2015. The postoperative pathological and immunohistochemical results showed traumatic neuroma. According to the postoperative follow-up, there were no symptoms of pain appearing again. Literature review The pain is obvious, and B ultrasonography is the most efficient way to find neuromas. Both conservative and operative therapy have their advantages and disadvantages. Conclusions There remain many unanswered questions in relation to the treatment of traumatic neuromas, and further research is required, although we have already had adequate understanding of traumatic neuromas.